Heterochromatin protein 1, a known suppressor of position-effect variegation, is highly conserved in Drosophila. - Clark, R F (1992)
The Su(var)205 gene of Drosophila melanogaster encodes heterochromatin protein 1 (HP1), a protein located preferentially within beta-heterochromatin. Mutation of this gene has been associated with dominant suppression of position-effect variegation. We have cloned and sequenced the gene encoding HP1 from Drosophila virilis, a distantly related species. Comparison of the predicted amino acid sequence with Drosophila melanogaster HP1 shows two regions of strong homology, one near the N-terminus (57/61 amino acids identical) and the other near the C-terminus (62/68 amino acids identical) of the protein. Little homology is seen in the 5' and 3' untranslated portions of the gene, as well as in the intronic sequences, although intron/exon boundaries are generally conserved. A comparison of the deduced amino acid sequences of HP1-like proteins from other species shows that the cores of the N-terminal and C-terminal domains have been conserved from insects to mammals. The high degree of conservation suggests that these N- and C-terminal domains could interact with other macromolecules in the formation of the condensed structure of heterochromatin.